2015
DOI: 10.1007/s00455-015-9606-5
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Pharyngeal Constriction and Post-swallow Residue

Abstract: Pharyngeal constriction has been proposed as a parameter that may distinguish functional from impaired swallows. We employed anatomically normalized pixel-based measures of pharyngeal area at maximum constriction, and the ratio of this measure to area at rest, and explored the association between these measures and post-swallow residue using the normalized residue ratio scale (NRRS). Videofluoroscopy data for 5 ml boluses of 22 % (w/v) liquid barium were analyzed from 20 healthy young adults and 40 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 14 publications
3
67
0
Order By: Relevance
“…Two patients were diagnosed with brain stem infarction and one patient was diagnosed with nasopharyngeal cancer post radiation. In our study, we found BD improved WPC, this result is consistent with the findings by Stokely et al, who postulated that interventions targeted on improving pharyngeal contraction should be effective in reducing post-swallow residue [27]. Lan et al, has proposed that BD served as a safe sensory stimulation to induce active resistance exercise in swallowing muscles, which in turn improved the pharyngeal driving force, further promoting UES relaxation and emptying pyriform sinus [4].…”
Section: Discussionsupporting
confidence: 92%
“…Two patients were diagnosed with brain stem infarction and one patient was diagnosed with nasopharyngeal cancer post radiation. In our study, we found BD improved WPC, this result is consistent with the findings by Stokely et al, who postulated that interventions targeted on improving pharyngeal contraction should be effective in reducing post-swallow residue [27]. Lan et al, has proposed that BD served as a safe sensory stimulation to induce active resistance exercise in swallowing muscles, which in turn improved the pharyngeal driving force, further promoting UES relaxation and emptying pyriform sinus [4].…”
Section: Discussionsupporting
confidence: 92%
“…Pharyngeal area: Unobliterated pharyngeal space, defined superiorly from the anterior‐superior corner of C2 to the base of tongue, anteriorly along the base of tongue, the valleculae, and epiglottis to the top of the arytenoid cartilage, inferiorly along the pyriform sinuses, and posteriorly along the entire posterior pharyngeal wall. This measure is routinely captured as a component of the maximum pharyngeal constriction ratio measures Vallecular space: Two‐dimensional measure of vallecular space defined by the base of tongue and vallecular border to the tip of the epiglottis.…”
Section: Methodsmentioning
confidence: 99%
“…To quantify gradients of laryngeal vestibule closure, a measure similar to the pharyngeal constriction ratio is needed. The pharyngeal constriction ratio was developed as a proxy that is indicative of the extent of pharyngeal constriction effectiveness by tracing the unobliterated or uncontracted area of pharyngeal space during maximum constriction and dividing this area by the pharyngeal space at rest . A greater pharyngeal area at maximum constriction leads to more post‐swallow residue in the valleculae or pyriform sinus .…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] A greater pharyngeal area at maximum constriction leads to more post-swallow residue in the valleculae or pyriform sinus. 26 Similar to the pharyngeal constriction ratio, a normalized laryngeal constriction ratio (LCR) could be useful in identifying the effect of airspace lost in the laryngeal vestibule during swallowing on any potential relationship to hyolaryngeal displacement and/or penetration or aspiration. Because we cannot currently directly measure every aspect of LVC during swallowing, this measurement may allow for further investigations to quantify closure patterns of laryngeal vestibule closure.…”
Section: Introductionmentioning
confidence: 99%